2021
DOI: 10.3390/act10120334
|View full text |Cite
|
Sign up to set email alerts
|

Wheel Deflection Control of Agricultural Vehicles with Four-Wheel Independent Omnidirectional Steering

Abstract: Due to the Fharsh working environment of wheeled agricultural vehicles in the field, it is difficult to ensure that all wheels make contact with the ground at the same time, which is easy to unequally distribute the yaw moments of each independent wheel. The commonly used vehicle lateral control methods are mostly controlled by coordinating the individual torque between different wheels. Obviously, this control method is not suitable for agricultural four-wheeled vehicles. The goal of this study was to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Ultimately, the initial values of the three parameters, K P , K I , and K D , for the fuzzy PID controller were set as K P0 = 55, K I0 = 102, and K D0 = 50. nature of the inspection robot's downhill speed control system and its susceptibility to external environmental factors like cable corrosion, wear, and wind force, it is challenging to establish an accurate mathematical model to control the walking wheel motor's speed. Hence, a combination of the Ziegler-Nichols tuning method and the ultimate gain method was used to adjust the parameters of the inspection robot's downhill speed control system [31]. The Ziegler-Nichols tuning method adjusts the proportional coefficient KP first, then the integral coefficient KI, and finally the derivative coefficient KD, to initially determine the range of values for the three parameters of the PID controller.…”
Section: Building An Adams/simulink Co-simulation Platformmentioning
confidence: 99%
“…Ultimately, the initial values of the three parameters, K P , K I , and K D , for the fuzzy PID controller were set as K P0 = 55, K I0 = 102, and K D0 = 50. nature of the inspection robot's downhill speed control system and its susceptibility to external environmental factors like cable corrosion, wear, and wind force, it is challenging to establish an accurate mathematical model to control the walking wheel motor's speed. Hence, a combination of the Ziegler-Nichols tuning method and the ultimate gain method was used to adjust the parameters of the inspection robot's downhill speed control system [31]. The Ziegler-Nichols tuning method adjusts the proportional coefficient KP first, then the integral coefficient KI, and finally the derivative coefficient KD, to initially determine the range of values for the three parameters of the PID controller.…”
Section: Building An Adams/simulink Co-simulation Platformmentioning
confidence: 99%
“…Q. Xu et al constructed a fuzzy PID controller to solve the problem of wheel deflection control of agricultural vehicles with four-wheel independent steering and conducted simulation experiments and field tests. The results showed that their steering control strategy has good real-time performance and effectively improves steering stability [16].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem of uneven distribution of yaw torque on each independent wheel of agricultural four-wheel vehicles, Xu et al [16] proposed a steering wheel steering angle control method using electric push rods as actuators, which combines PID control and fuzzy regulation for controlling. The feasibility and rationality of the designed wheel steering mechanism were verified through dynamic simulation and virtual simulation of fuzzy PID controller.…”
Section: Introductionmentioning
confidence: 99%